Adipokines and Insulin Resistance in Young Adult Survivors of Childhood Cancer. (24th April 2016) - Latoch, Eryk; Muszynska-Roslan, Katarzyna; Panas, Agata; Panasiuk, Anna; Sawicka-Zukowska, Malgorzata; Zelazowska-Rutkowska, Beata; Zabrocka, Ewa; Krawczuk-Rybak, Maryna
Abstract : We examined the association between adipokines (leptin, adiponectin, and resistin), radiotherapy, measurement of body fat, and insulin resistance among young adult survivors of childhood cancer (CCS). Materials and Methods. Seventy-six survivors were included (mean age 24.1 ± 3.5 years). Insulin resistance (IR) was calculated using the homeostasis model assessment (HOMA-IR). The serum levels of adipokines were assayed by immunoassays. Fat mass was evaluated by DXA. Results. Mean adiponectin level and mean body FAT were higher in the examined females than in males (10009 ± 6367  ng/mL versus 6433 ± 4136  ng/mL, p < 0.01 ; 35.98 ± 9.61 % versus 22.7 ± 7.46 %, p < 0.001 ). Among CCS, one of 75 patients met the criteria of insulin resistance, and in 14 patients there was impaired fasting glucose. The multiple regression model for females showed that leptin/adiponectin ratio (LA ratio) significantly affected HOMA-IR (increase of 0.024 per each unit of LA ratio; p < 0.05 ). Radiotherapy had no effect on serum adipokines and IR. Conclusion. The observed results support the hypothesis that adiponectin might be associated with insulin resistance and it can not be ruled out that changes in the mean level of adiponectin per FAT mass or leptin/adiponectin ratio may precede the occurrence of insulin resistance in the future.